A tale of PN17 listed companies in Malaysia - Ng, Choon Jin (2021)
This study investigates and reviews the causes of listed companies being classified under PN17 in Malaysia in the period 2006 to 2015. The scope of this study includes the identification of the causes of classification under PN17 as prescribed by Bursa Malaysia (“Bursa”); the actions taken by listed companies when classified as PN17; and finally the consequences and outcomes after a company has been classified under PN17. Both the Altman Z-scores and Taffler Z-scores were computed for the companies in question in order to identify whether these Z-scores are statistically significant in determining the probability of a company being classified under PN17. This research shows that the most common causes of PN17 classification are poor liquidity management and weak profitability in a listed company. In sum, this study shows that the most important thing for a company seeking to mitigate the potentially serious consequences of classification under PN17 is to obtain approval for a regularisation plan from the SC or Bursa.